"Nuns, yoginis, saints and singers: women's renunciation in South Asia" - "Khandelwal, Meena (ed.); Housner, Sondra L. (ed.); Gold, Ann" (New Delhi, 2007)
This volume brings together new ethnographic research on South Asian women who have abandoned worldly life for spiritual pursuits. All have renounced some combination of the following: marriage, sex, procreation, kin, financial security, concern with beauty, and sensual pleasures. Documenting contemporary women s experiences with intimate ethnographic narratives, this book offers feminist insights into Jain, Buddhist, Hindu, and Baul ascetic traditions. This collection also considers the hardships endured by women committed to religious paths more commonly taken by men and offers a refreshing antidote to the relentless image of South Asian women as dependent on male kin and defined by their sexual and procreative roles.
Keywords: Women-South Asia-Ethnographic studies